2020
DOI: 10.3390/foods9060814
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Consumer Evaluation of Cocoa Bean Shell-Functionalized Biscuits Adapted for Diabetic Consumers by the Replacement of Sucrose with Tagatose

Abstract: The cocoa bean shell (CBS), a by-product of the cocoa industry, has been reported to be rich in fiber and polyphenols, which could contribute to reducing the metabolism of sugars and glucose adsorption. The production of CBS-based biscuits in which sucrose is replaced with tagatose (a low-glycemic sugar with prebiotic properties), benefiting diabetic consumers, is proposed. Six prototype biscuits were produced using sucrose, tagatose, and CBS powder at 0%, 10%, and 20% as a wheat flour replacement. Biscuits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
4
19
1
1
Order By: Relevance
“…The present study, which is a continuation of a previous one [ 11 ], highlights the potential of using CBS as a functional ingredient for high-fiber functional biscuits, with the possibility of adapting this product for diabetic consumers through the addition of tagatose. It was demonstrated that the substitution of sucrose with tagatose as a sweetener did not affect the bioavailability of bioactive compounds contained in the CBS-based biscuits.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The present study, which is a continuation of a previous one [ 11 ], highlights the potential of using CBS as a functional ingredient for high-fiber functional biscuits, with the possibility of adapting this product for diabetic consumers through the addition of tagatose. It was demonstrated that the substitution of sucrose with tagatose as a sweetener did not affect the bioavailability of bioactive compounds contained in the CBS-based biscuits.…”
Section: Discussionsupporting
confidence: 63%
“…Mostly, they combine with the cell wall components that constitute dietary fiber [ 25 , 26 ]. Dietary fiber in the biscuits with zero CBS added (control biscuits) has been reported to account for 2.48–2.79% of the dried product [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Friability is a salient textural characteristic for biscuits [ 41 , 42 ]. Tough, non-crumbly biscuits have low acceptance values in consumer tests [ 43 ]. This variation of breaking strength was significant when comparing control with AS20 and was due to the high presence of fiber in the almond skins.…”
Section: Resultsmentioning
confidence: 99%